Good masters! Sweet Ladies! : voices from a medieval village - Schlitz, Laura Amy.; Byrd, Robert (Cambridge, Mass. : Candlewick Press, 2007)
A collection of short one-person plays featuring characters, between ten and fifteen years old, who live in or near a thirteenth-century English manor.
Hugo, the Lord's nephew -- Taggot, the blacksmith's daughter -- Will, the plowboy -- Alice, the shepherdess -- Thomas, the doctor's son -- Constance, the pilgrim -- Mogg, the villein's daughter -- Otho, the miller's son -- Jack, the half-wit -- Simon, the knight's son -- Edgar, the falconer's son -- Isobel, the Lord's daughter -- Barbary, the mud slinger -- Jacob Ben Salomon, the moneylender's son and Petronella, the merchant's daughter -- Lowdy, the varlet's child -- Pask, the runaway -- Piers, the glassblower's apprentice -- Mariot and Maud, the glassblower's daughters -- Nelly, the sniggler -- Drago, the tanner's apprentice -- Giles, the beggar.
A Junior Library Guild selection
Includes bibliographical references (p. 82-85).
Keywords: Middle Ages -- Juvenile drama; Monologues -- Juvenile literature; Children's plays, American; Monologues -- Juvenile fiction; Theater -- Fiction; Newbery Medal -- Juvenile literature